Pengaruh Profitabilitas (ROA), Earning Per Share, Solvabilitas (DER), Market Value Added (MVA), dan Kepemilikan Manajerial Terhadap Harga Saham Sektor Keuangan Sub Sektor Bank - Albab, Farah Nisa Ul; Mahendra, Widodo Arif; Nurrasyidin, Muhammad (Journal of Culture Accounting and Auditing, 2025)
The purpose of this study is to analyze the influence of profitability (ROA), earning per share, solvency (DER), market value added (MVA), and managerial ownership on stock prices. Purposive sampling is used to determine samples from the population of companies listed on the IDX in the 2019–2023 time range. The data was analyzed with IBM SPSS version 27. The findings of the study reveal that market value added has no effect on stock prices, while profitability (ROA), earning per share, solvency (DER), and managerial ownership have an effect on stock prices.